Trade in Intermediate Goods and Services - Miroudot, Sébastien (OECD Publishing, 2009)
This study analyses trade flows in intermediate goods and services among OECD countries and with their main trading partners. Combining trade data and input-output tables, bilateral trade in intermediate goods and services is estimated according to the industry of origin and the using industry for the period 1995-2005. Trade in intermediate inputs takes place mostly among developed countries and represents respectively 56% and 73% of overall trade flows in goods and services. Gravity regressions indicate that in comparison to trade in final goods and services, imports of intermediates are more sensitive to trade costs and are less attracted by bilateral market size. Further findings are that the activities of multinational enterprises can be associated with higher trade flows of intermediate inputs and with a higher ratio of foreign to domestic inputs in using industries. Results from production function regressions and from a stochastic frontier analysis suggest that a higher share of imported inputs leads to productivity gains in domestic industries and reduces inefficiencies in the use of technology
Keywords: Trade